JavaServer pages : pocket reference. - Bergsten, Hans, ....- (Beijing : O'Reilly, 2001)
Samenvatting:JavaServer Pages (JSP) is harmonizing how web designers and programmerscreate dynamic web pages. JavaServer Pages Pocket Reference is theperfect companion volume to O'Reilly's best-selling JavaServer Pages.This book provides detailed coverage of JSP syntax and processing,directive elements, standard action elements, scripting elements,implicit objects, custom actions, tag library description creation, andWARs.
Keywords: Java (programmeertaal).; Webdesign; Www world wide web